Effect Of Educator Qualifications On Educational Institutions - Imam Tabroni; Alvioni Nadea Fikriah; Dida Nurbaida; Fadila Qoulan Sadida (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The Influence Of Educator Qualifications On Educational Institutions . We adopted this title based on an idea from one of our supervisors, because there are still many schools that are actually held by school principals who have not/have not yet reached the undergraduate level. This study also aims to see and describe the influence of educator qualifications on PAUD educational institutions from their experience, teaching methods, and last level of education. This observation was carried out using qualitative research methods, we observed by looking, observing and reading references to articles and journals related to the problems we raised. The population in this study was the principal who had a SMA/SMK education. We collect data / research results from the observations we have made, the results of the studies that we observe on average from the number of PAUD school principals have not achieved the qualification of a bachelor’s degree in early childhood education, why do you need a bachelor’s degrees? Because to become a school principal, you must meet general qualifications and also special qualifications, one of which is a bachelor’s education (S1) or a minimum of four diploma (D4) and also the teaching experience for TK/PAUD/RA is at least 3 years.